Factors influencing the transition from pediatric to adult care: A scoping review of the literature to conceptualize a relevant education program. Issue 10 (October 2017) - Morsa, Maxime; Gagnayre, Rémi; Deccache, Carole; Lombrail, Pierre
Highlights: An integrative framework of factors influencing transition is proposed. Conceptualization of patient education program for transition is now possible. Psychosocial dimensions are not enough included on the research of transition. Patient education program for transition could include a support to identity development. Abstract: Objective: To give a comprehensive overview of the factors that influence the transition from pediatric services to adult care, and to conceptualize a relevant education program. Method: An evaluation grid was used to analyze the literature and classify factors depending on whether they were related to the patients, to the health care organization, to health care personnel, to the interaction between medical staff and patient, or to the illness and its treatment. Results: We based our analysis on a selection of 20 publications. The following factors were identified and classified in an integrative framework: self-management skills, trust in adult care, the feeling of self-efficacy, social support, the patient's gender and social position, the trust between child carers and adult carers, interdisciplinary cooperation, and the medical staff's consideration of the patient's projects. Conclusions and practice implications: The current analysis makes it possible to formulate educational aims and to design a way of integrating them to a transition plan. However, the collected studies mainly focus on knowledge of the illness, on treatment, and on the health care system. Psychosocial dimensions at play at the time of the transition – such as identity development – are not sufficiently explored in the research.